1990
DOI: 10.1063/1.345212
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the hyperbolic electron mirror as a correcting element for spherical and chromatic aberration in electron optics

Abstract: The spherical and chromatic aberrations of a converging electron mirror are of opposite sign from those of electron lenses. This important property makes it possible in principle to compensate the aberrations of electron lenses by means of an electron mirror and to design electron microscopes based on a corrected optics system incorporating an electron mirror. In this paper the properties of the hyperbolic electron mirror are calculated, and the conditions for simultaneous correction of spherical and chromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 11 publications
0
43
0
1
Order By: Relevance
“…With a normal distribution of emission energies spread out over ∆E = 1 eV, typical aberration coefficients in the range C s ≈ C c ≈0.4 m [64], and at an optimally limited aperture angle of 0.7 mrad, this formula predicts a best resolution of 10 nm, an order of magnitude greater than the diffraction limit.…”
Section: Aberration Correction 1 Electron Optics and Image Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a normal distribution of emission energies spread out over ∆E = 1 eV, typical aberration coefficients in the range C s ≈ C c ≈0.4 m [64], and at an optimally limited aperture angle of 0.7 mrad, this formula predicts a best resolution of 10 nm, an order of magnitude greater than the diffraction limit.…”
Section: Aberration Correction 1 Electron Optics and Image Resolutionmentioning
confidence: 99%
“…[74,[79][80][81]), reflecting electron trajectories so that r(z) is no longer a one-to-one function (mirrors, cf. [64,74,[82][83][84]), or using time-varying fields (cf. [74,85,86]).…”
Section: Aberration Correction 1 Electron Optics and Image Resolutionmentioning
confidence: 99%
“…To improve the signal to noise ratio in the images the design of the microscope optics must be optimized to maximize its electron transmission function. To achieve a high electron transmission simultaneously with a high spatial resolution, our new X-PEEM will include an electrostatic hyperbolic electron mirror [14] to correct the chromatic and spherical aberration of the electrostatic lenses and of the accelerating field between the sample and the objective. In addition it will work at substantially higher voltage (30 kV) and use a much more efficient YAG-cooled CCD detector instead of the present channel plate/phosphor/CCD combination currently used.…”
Section: Polymers Blendsmentioning
confidence: 99%
“…More complete analysis, especially for LEEM [6], has shown that 10nm lateral resolution is possible with uncorrected lenses, and possibly better resolution with advances in electron optics [7].…”
Section: Introductionmentioning
confidence: 99%